1997
DOI: 10.1093/ndt/12.7.1376
|View full text |Cite
|
Sign up to set email alerts
|

The pulsatility index and the resistive index in renal arteries. Associations with long-term progression in chronic renal failure

Abstract: PI and RI correlated to the severity of the renal disease, as reflected by the rate of decline in reciprocal serum creatinine during antihypertensive treatment. The median RI or PI value could separate the patients into groups one of slow and another of fast progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
124
0
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 12 publications
5
124
0
6
Order By: Relevance
“…19 Hypertension may cause nephrosclerosis or glomerulosclerosis, reducing the intrarenal vascular surface area and increasing vascular resistance even in the unaffected kidney. 20 The evaluation of RRI in hypertensive patients reveals significantly higher values than normotensive subjects, even without overt nephropathy. 21 Nevertheless, lower RRI values were associated with low renal and CV target organ damage.…”
Section: Discussionmentioning
confidence: 98%
“…19 Hypertension may cause nephrosclerosis or glomerulosclerosis, reducing the intrarenal vascular surface area and increasing vascular resistance even in the unaffected kidney. 20 The evaluation of RRI in hypertensive patients reveals significantly higher values than normotensive subjects, even without overt nephropathy. 21 Nevertheless, lower RRI values were associated with low renal and CV target organ damage.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies revealed that the RI was a useful predictor of renal dysfunctions [11][12][13][14][15][16] and correlated significantly with organ damage. Measurement of RI in addition to low-grade albuminuria is reportedly useful for target organ damage screening in patients with resistant Blood pressure variability and renal function T Kawai et al hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…[11][12][13][14][15][16] We previously reported that the RI might be a more efficacious parameter for the evaluation of very early renal damage than estimated glomerular filtration rate (eGFR). 17 It is thought that renal vascular damage caused by atherosclerotic risk factors such as hypertension and variability of BP could be evaluated more precisely by the RI.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the renal resistive index (RI) calculated from pulsed Doppler flow at the interlobular arteries have been proposed for evaluating the renal microcirculation. [1][2][3] However, we still lack simple tools for evaluating the coronary and cerebral microcirculations. In this context, study of the cutaneous microcirculation has been the subject of numerous investigations.…”
Section: Introductionmentioning
confidence: 99%